Pengaruh Kemasan Produk, Promosi Penjualan dan Ulasan Pelanggan Online terhadap Keputusan Pembelian Skincare Skintific pada Platform Tiktok: Studi Kasus di Kota Banda Aceh - Putri Rizki; Thasrif Murhadi; Fani Sartika (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to determine the influence of product packaging, sales promotions, and online customer reviews on Skintific skincare purchase decisions on the TikTok platform, both partially and simultaneously. The method used in this study is a quantitative approach. The sample consisted of 96 respondents who were selected as research participants. Data collection was carried out using questionnaire statements designed to measure respondents’ perceptions of each research variable. The data obtained were then analyzed using multiple linear regression analysis to examine the relationship between independent and dependent variables. In addition, hypothesis testing was conducted using the t-test to determine the partial effect of each independent variable and the F-test to determine the simultaneous effect of all independent variables on the dependent variable. The results of the study indicate that product packaging has a significant partial effect on Skintific skincare purchase decisions on the TikTok platform. Sales promotions also have a significant partial effect on purchase decisions, as they influence consumer interest and purchasing behavior. Furthermore, online customer reviews significantly affect purchase decisions by providing social proof and influencing consumer trust. Simultaneously, product packaging, sales promotions, and online customer reviews have a significant combined effect on Skintific skincare purchase decisions on the TikTok platform, indicating that these variables jointly play an important role in shaping consumer purchasing behavior.